2013
DOI: 10.1051/0004-6361/201321218
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fields around evolved stars: further observations of H2O maser polarization

Abstract: Context.A low-or intermediate-mass star is believed to maintain a spherical shape throughout the evolution from the main sequence to the asymptotic giant branch (AGB) phase. However, many post-AGB objects and planetary nebulae exhibit non-spherical symmetry. Several candidates have been suggested as factors that can play a role in this change of morphology, but the problem is still not well understood. Magnetic fields are one of these possible agents. Aims. We aim to detect the magnetic field and infer its pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 48 publications
7
28
0
Order By: Relevance
“…Circular polarization of non-Zeeman origin would imply a significantly lower magnetic field strength than required for Zeeman circular polarization of observed SiO masers. We note that the resonant scattering mechanism proposed by Houde (2014) requires a magnetic field strength in the foreground lower-density gas that is not inconsistent with that derived from H 2 O maser observations (Vlemmings et al 2005;Leal-Ferreira et al 2013).…”
Section: Introductionsupporting
confidence: 54%
“…Circular polarization of non-Zeeman origin would imply a significantly lower magnetic field strength than required for Zeeman circular polarization of observed SiO masers. We note that the resonant scattering mechanism proposed by Houde (2014) requires a magnetic field strength in the foreground lower-density gas that is not inconsistent with that derived from H 2 O maser observations (Vlemmings et al 2005;Leal-Ferreira et al 2013).…”
Section: Introductionsupporting
confidence: 54%
“…Very recently, Leal-Ferreira et al (2013) have used polarization of H 2 O maser emissions in a sample of AGB stars to present the new panorama for magnetic fieldstrength dependence along r, the radial distance to the star (see their Fig. 5).…”
Section: A Coherent View Of the Magnetic Field At The Surface And In mentioning
confidence: 99%
“…However, only one AGB star is known to show a fast rotation (V Hya; Barnbaum et al 1995), and generally slow rotation rates are found among white dwarf stars (Kawaler et al 1999); (ii) a bipolar magnetic field causes the wind to become denser at the magnetic equator (Matt et al 2000). Surface magnetic fields have been recently reported for some AGB stars (Vlemmings et al 2011;Leal-Ferreira et al 2013;Lèbre et al 2014), but there is no observational evidence for stellar magnetic fields to shape stellar AGB winds; (iii) the most common explanation is gravitational focusing of the AGB wind on the orbital plane of a companion. This scenario is supported by hydrodynamic simulations (Mastrodemos & Morris 1999;Kim & Taam 2012a) and by observations (e.g.…”
Section: Origin Of the Elliptical Emissionmentioning
confidence: 99%